Radical Acceptance of Reality: Putting DBT®-A Skill Groups Online During the COVID-19 Pandemic: A Qualitative Study - Bock, Mercedes M.; Graf, Theres; Woeber, Verena; Kothgassner, Oswald D.; Buerger, Arne; Plener, Paul L. (Frontiers in Psychiatry, 2022)
Introduction Emotion dysregulation is a common challenge pertaining to numerous psychiatric disorders in adolescence and is associated with increased morbidity and mortality. Dialectical Behavior Therapy for Adolescents (DBT-A) has been shown to be an effective treatment, especially in the reduction of self-harm and suicidality. Measures in relation to COVID-19 set strict limits on physical contacts with patients. To continuously provide evidence-based care to patients suffering from emotion dysregulation, we offered two online DBT-A skills groups in a video-group-call format. Objective We aimed at assessing our online DBT-A skills groups, collect according up- and downsides and form a basis for advancement of this form of treatment provision. Also, impact of the COVID-19 pandemic on patients was assessed. Methods A physical DBT-A skills group was switched to a video-group-call format and a second group was initiated de novo online. After five sessions, patients engaged in structured group discussions to reflect experiences. Discussion content was analyzed via Inductive Category Formation within the Framework of Qualitative Content Analysis. Results Patients unanimously found the COVID-19 pandemic challenging, but also reported differentially on its impact. Downsides were balanced by subjective “gains” in time and a perceived reduction of stress. Technical problems of the online format were discussed, but did not limit the positive experience of still receiving treatment. Patients of both online DBT-A skills groups valued the offer, felt connected and reported benefits from the treatment. The transition group additionally discussed changes in structure and content of the group sessions after the switch to online meetings and reflected differential functions of the group. Discussion Although the sample size is small and conclusions are drawn from Inductive Qualitative Content Analysis, the presented results are of interest. In our investigation, video-group-calls were both safe and beneficial for patients. This alternative to physical meetings is not only interesting for further waves of the current pandemic, but also for service provision in remote areas with limited access to specialized care. Further research is needed to challenge and refine our results and to explore extensions to “basic” video-group-calls, such as “break-out-sessions”, blended therapy or real time supervision within an online session.